2020
DOI: 10.1111/cod.13598
|View full text |Cite
|
Sign up to set email alerts
|

Occupational and non‐occupational allergic contact dermatitis to hair dyes in Greece. A 10‐year retrospective study

Abstract: Background Oxidative hair dyes are an important source of chemical exposure and a major risk factor for the development of occupational and non‐occupational allergic contact dermatitis (ACD) worldwide. Objective To identify the frequency of common allergens associated with occupational and non‐occupational ACD to hair dyes during the last 10 years, in Greece. Methods We retrospectively reviewed the medical records of patients with suspected ACD to hair dyes from 2010–2019. All patients with patch‐test‐confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 61 publications
2
19
0
Order By: Relevance
“…The most common occupational allergens for hairdressers in our study were PPD, toluene‐2,5‐diamine sulfate (PTD), and other para‐group hair dye allergens, and ammonium persulfate in hair bleach, similar to previous reports 29,30,33,35,37‐40 . Ammonium persulfate was the predominating allergen in some studies 38 .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The most common occupational allergens for hairdressers in our study were PPD, toluene‐2,5‐diamine sulfate (PTD), and other para‐group hair dye allergens, and ammonium persulfate in hair bleach, similar to previous reports 29,30,33,35,37‐40 . Ammonium persulfate was the predominating allergen in some studies 38 .…”
Section: Discussionsupporting
confidence: 89%
“…Hairdressers were the second most common occupational group in our series. Hairdresser apprentices were almost as frequently sensitized to hairdresser chemicals as professionals in our study, accounting for the young age and early onset of OACD, a well‐defined feature for hairdressers 29‐32 As an exception to the literature, 30‐36 male patients predominated among hairdressers in our series because men are more frequently employed as hairdressers in Turkey. Atopics were slightly more frequent among hairdresser apprentices than professionals, supporting the so‐called “healthy worker effect,” which indicated those who leave their job at an early stage of occupation due to atopy‐related morbidity 30,34 …”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Ammonium persulfate (or AP) is one of the main culprits of ACD in hairdressers; this has been demonstrated on several series in which this allergen has shown positive results in a greater proportion of hairdressers when compared with controls and customers 1‐3 . ACD in hairdressers is commonly observed as hand eczema, whereas other topographies are affected in a lower proportion of patients, which makes the use of gloves an important part of the preventive measures 4 .…”
Section: Discussionmentioning
confidence: 99%
“…The presence of contact allergies is closely attributed to the potent skin sensitizers contained in hair dyes, such as aromatic amines including PPD, a prevalent hair dye ingredient. 43 However, using permanent hair dyes containing PPD at concentrations ≤0.67% is unlikely to induce skin sensitization. 44 Recently, Goebel and co-workers 45 found that a methoxymethyl side chain introduced into PPD not only reduced the sensitizing intensity and the risk of allergic induction but also resulted in excellent hair coloring performance.…”
Section: Hair Dye-induced Toxicities and Adverse Health Effectsmentioning
confidence: 99%